Putusan Pengadilan Agama Lebong Terhadap Dispensasi Nikah (Tinjauan Maqashid Al-Syari’ah) - Putra, Rian Monda; Nofialdi, Nofialdi; Yunarti, Sri (Ikhtisar: Jurnal Pengetahuan Islam, 2024)
Marriage is sunnatullah as a human being who needs a partner with the aim of producing offspring. However, among the community, sometimes the implementation of marriage is carried out by underage brides, while the marriage requires mental and material readiness that is able to be responsible for carrying out the household. This study aims to reveal the implementation of underage marriages that occur in Lebong society. This research uses qualitative methods with a form of field research and uses normative and empirical research models. This research resulted in the findings of the Lebong Religious Court making decisions and providing dispensation for the implementation of marriage, including Amendments to Law Number 1 of 1974 concerning marriage and Pregnancy outside marriage. The basis for the Judge's consideration in making decisions and providing dispensation to the community who applied for marriage, namely Supreme Court Regulation Number 5 of 2019 and other grounds that need to be considered by the Religious Court Judge, such as girls who are already pregnant first, children are no longer in school, children are already working and so on. Based on the analysis of maqasid Al-Syariah review, it can be reviewed from the level of dharuriyyaat, and Hajiyyaat. However, the elements of the level that need to be maintained in maqashid al-syari'ah, namely Maintaining Religion, Maintaining Life, Maintaining Property and Maintaining Descent.